Linking physicochemical properties and sensory data in fibre-enhanced chocolate-based systems - Mouraka, Panagiota (2025)
Sugar consumption is an increasingly significant public health concern, motivating the confectionery industry to explore alternative sweetening strategies in chocolate formulation. Chocolate is a mechanically complex fat-based suspension comprising sugar, cocoa, and milk solids, and is highly appreciated for its distinctive sensory properties and oral processing behaviour. These attributes contribute to consumer perceptions of chocolate as an ‘indulgent’, ‘restful’, and ‘luxurious’ treat. Importantly, many of these sensory qualities are linked to the presence of sucrose crystals, their size, solubility, and characteristic sweetness. The challenge lies in reducing or replacing sucrose without compromising the sensory experience or structural integrity of the final product. This thesis addresses this challenge through a comprehensive, multi-methodological research programme with two primary objectives: (i) to investigate the mechanical and sensory attributes of fat-based suspensions enriched with dietary fibres, and (ii) to explore ball milling as a modification technique to enhance the functional performance of fibres for sugar reduction in chocolate.